2014
DOI: 10.1103/physrevb.89.014425
|View full text |Cite
|
Sign up to set email alerts
|

Electric field tuning of phase separation in manganite thin films

Abstract: In this paper, we investigate the electric field effect on epitaxial Pr 0.65 (Ca 0.75 Sr 0.25 ) 0.35 MnO 3 thin films in electric double-layer transistors. Different from the conventional transistors with semiconducting channels, the sub(micrometer)-scale phase separation in the manganite channels is expected to result in inhomogeneous distribution of mobile carriers and local enhancement of electric field. The field effect is much larger in the low-temperature phase separation region compared to that in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 93 publications
(136 reference statements)
1
51
1
Order By: Relevance
“…[49] In case of 13 nm films, the attained large values of surface charge up to 250 µC cm −2 enabled a maximum reversible modulation in magnetization of about 30% at room temperature. Several other comprehensive studies contributed to disentangle the complex relationship between charge carrier doping and magnetism in electrolyte-gated magnetic oxides, including investigations on LCMO, [80,91] LSMO, [43,156] LaMnO 3 , [67] Pr 1−x (Ca 1−y Sr y ) x MnO 3 , [157,158] LSCO, [82] Fe 3 O 4 , [159] and γ-Fe 2 O 3 . [42] In addition, the magnetic response was flexibly modulated in-phase or antiphase with respect to the induced surface charge by judiciously adjusting the applied bias voltage (see Figure 4b).…”
Section: Me Coupling Via Charge Carrier Dopingmentioning
confidence: 99%
“…[49] In case of 13 nm films, the attained large values of surface charge up to 250 µC cm −2 enabled a maximum reversible modulation in magnetization of about 30% at room temperature. Several other comprehensive studies contributed to disentangle the complex relationship between charge carrier doping and magnetism in electrolyte-gated magnetic oxides, including investigations on LCMO, [80,91] LSMO, [43,156] LaMnO 3 , [67] Pr 1−x (Ca 1−y Sr y ) x MnO 3 , [157,158] LSCO, [82] Fe 3 O 4 , [159] and γ-Fe 2 O 3 . [42] In addition, the magnetic response was flexibly modulated in-phase or antiphase with respect to the induced surface charge by judiciously adjusting the applied bias voltage (see Figure 4b).…”
Section: Me Coupling Via Charge Carrier Dopingmentioning
confidence: 99%
“…[23][24][25][26] XRD measurements were performed using a X-ray diffractometer (SmartLab, Rigaku) in the highresolution mode. Transport and gating measurements were carried out in a physical property measurement system (PPMS-14 T, Quantum Design) with externally connected meters.…”
mentioning
confidence: 99%
“…[83] For instance, Lee et al fabricated EDLT using STO (100) as the channel and Al/Ti/Au as electrodes. The sensitivity of the electric field effect is dependant on the applied magnetic field, and a maximum resistance modulation of 2.5 times was achieved at 80 K with a magnetic field of 1.38 T. [92] A gate-controlled Kondo effect was demonstrated in the 2D electron system, which indicates that this system is a combination of magnetic Ti 3+ ions (e.g., localized and unpaired electrons) and delocalized electrons that partially fills the Ti 3d conduction band.…”
Section: Oxide Perovskite As N-and P-type Channelsmentioning
confidence: 97%
“…[85] Multiple electrolytes were used as dielectric electrolyte, including polyethylene oxide with KClO 4 , [80] N,N-diethyl-N-(2methoxyethyl)-N-methylammonium bis (trifluoromethyl sulphonyl)-imide (DEME-TFSI), [82] and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)amide (EMI-TFSA). The EDLT with the strained CMO exhibited a conductivity modulation of about 120 times at 50 K and four times at room temperature upon an applied gate voltage of 2 V. [91] Lourembam et al [92] demonstrated EDLT using Pr 0.65 (Ca 0.75 Sr 0.25 ) 0.35 MnO 3 thin film as the channel, (LaAlO 3 ) 0.3 -(Sr 2 AlTaO 6 ) 0.7 (001) as substrate, Au as the electrode, and ionic liquid DEME-TFSI as the gate dielectric. The electrolyte was synthesized by gelation of poly(styrene-block-methylmethacrylateblock-styrene) (PS-PMMA-PS) in an ionic liquid EMI-TFSA.…”
Section: Oxide Perovskite As N-and P-type Channelsmentioning
confidence: 99%
See 1 more Smart Citation